2013
DOI: 10.1016/j.ajhg.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variants at the 11q13 Risk Locus for Breast Cancer Regulate Cyclin D1 Expression through Long-Range Enhancers

Abstract: Analysis of 4,405 variants in 89,050 European subjects from 41 case-control studies identified three independent association signals for estrogen-receptor-positive tumors at 11q13. The strongest signal maps to a transcriptional enhancer element in which the G allele of the best candidate causative variant rs554219 increases risk of breast cancer, reduces both binding of ELK4 transcription factor and luciferase activity in reporter assays, and may be associated with low cyclin D1 protein levels in tumors. Anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(220 citation statements)
references
References 46 publications
(48 reference statements)
11
202
3
4
Order By: Relevance
“…4 Using 3C, we (B) Intron-exon structures of CUPID1 and CUPID2 transcripts identified by RNA CaptureSeq in MCF7 cells with or without estrogen stimulation. RefSeq lncRNA gene LINC01488 (CUPID1) and predicted lncRNA AP000439.3 (CUPID2) are shown in green, and CUPID1 and CUPID2 transcripts verified by PCR in MCF7 cells are indicated by red arrows ( Figure S2).…”
Section: Results Lncrnas Expressed From the 11q13 Breast Cancer Riskmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Using 3C, we (B) Intron-exon structures of CUPID1 and CUPID2 transcripts identified by RNA CaptureSeq in MCF7 cells with or without estrogen stimulation. RefSeq lncRNA gene LINC01488 (CUPID1) and predicted lncRNA AP000439.3 (CUPID2) are shown in green, and CUPID1 and CUPID2 transcripts verified by PCR in MCF7 cells are indicated by red arrows ( Figure S2).…”
Section: Results Lncrnas Expressed From the 11q13 Breast Cancer Riskmentioning
confidence: 99%
“…4 However, cyclin D1 also plays a role in HR-mediated DNA repair (HRR), a function independent of its role in cell-cycle control. 28 Given this and the fact that pathway analyses indicated that CUPID1-and CUPID2-regulated genes affect DNA repair and recombination, we hypothesized that PRE1 might act as an enhancer of other genes in the HRR pathway, including CUPID1 and CUPID2.…”
Section: Effect Of Cupid1 and Cupid2 On Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Independent loci for breast and renal cancer have been shown to interact with the promoter of the cyclin D (CCND1) gene located $130 and $216 kb downstream, and possibly regulate its expression in an allele-specific manner (43,44).…”
Section: Discussionmentioning
confidence: 99%